2018
DOI: 10.1002/ejp.1215
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned pain modulation using painful cutaneous electrical stimulation or simply habituation?

Abstract: Painful cutaneous electrical stimulation leads to moderate habituation of pain and evoked potential amplitudes, but the conditioned pain modulation effect using this method is significantly larger, which might indicate a different mechanism in central processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
25
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 42 publications
7
25
2
Order By: Relevance
“…In accordance with our previous studies [ 20 , 36 ], the amplitudes of the PCES-induced evoked potentials were significantly reduced both during and after CS application, though, the reduction did not correlate with the changes in TS pain intensity. The latter is in contrast to our first study [ 20 ], but in line with following studies we performed using the same CPM testing paradigm [ 36 ]. This might be due to the less pronounced mean CPM-effect in the current study compared to the previous [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In accordance with our previous studies [ 20 , 36 ], the amplitudes of the PCES-induced evoked potentials were significantly reduced both during and after CS application, though, the reduction did not correlate with the changes in TS pain intensity. The latter is in contrast to our first study [ 20 ], but in line with following studies we performed using the same CPM testing paradigm [ 36 ]. This might be due to the less pronounced mean CPM-effect in the current study compared to the previous [ 20 ].…”
Section: Discussionsupporting
confidence: 92%
“…This might be due to the less pronounced mean CPM-effect in the current study compared to the previous [ 20 ]. Notably, the CPM-effect had a similar magnitude in both previous studies [ 20 , 36 ], but the correlation between pain intensity and the amplitudes of the PCES-induced evoked potentials was significant only in one of them.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In summary, using the recently introduced novel CPM-paradigm we demonstrated that both PCES-induced pain and PCES-EP amplitudes can be reduced not only by CPM 20,39 but also during distraction by a cognitive task. While the amount of pain relief induced by CPM and distraction by a cognitive task did not differ signi cantly during both interventions, the decrease of PCES-EP amplitudes after distraction by a cognitive task was slightly more pronounce than during CPM.…”
Section: Discussionmentioning
confidence: 71%